Transfer and persistence of maternal antibodies against Theileria annulata in calves - PRASANTHI, C S; JAGANNATH, M S; RAJASEKHAR, M; RAHMAN, S ABDUL (The Indian Journal of Animal Sciences, 2013)
The transfer of matemal antibodies to calves born to Theileria annulata- vaccinated (Rakshavac-T) and unvaccinated dams was estimated by avidin-biotin ELISA test in 3 breeds of cattle. Red Sindhi breed showed higher optical density (OD) values followed by Holstein-Friesian. The lowest values were observed in Jersey cattle. The investigation revealed significant higher antibody levels in calves born to vaccinated dams with lower values in calves of unvaccinated dams. The antibody titre of calves showed a progressive increase till 30 days of birth. It attained the peak at 60 days and gradually declined from 90 days onwards in calves of both groups.